2016
DOI: 10.1002/pro.2871
|View full text |Cite
|
Sign up to set email alerts
|

A de novo protein confers copper resistance in Escherichia coli

Abstract: To survive environmental challenges, biological systems rely on proteins that were selected by evolution to function in particular cellular and conditional settings. With the advent of protein design and synthetic biology, it is now possible to construct novel proteins that are not biased by eons of selection in natural hosts. The availability of these sequences prompts us to ask whether natural biological organisms can use na€ ıve-non-biological-proteins to enhance fitness in stressful environments. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…For future goals in synthetic biology, the most significant findings showed that several of the binary patterned proteins provide life-sustaining functions in vivo. One protein enables E. coli to resist otherwise toxic concentrations of copper [16], while others rescue auxotrophic cells harboring deletions of conditionally essential genes [9,17,18]. Recently, we described a novel protein that supports cell growth by functioning as a bona fide enzyme, both in vitro and in vivo [19].…”
Section: Introductionmentioning
confidence: 99%
“…For future goals in synthetic biology, the most significant findings showed that several of the binary patterned proteins provide life-sustaining functions in vivo. One protein enables E. coli to resist otherwise toxic concentrations of copper [16], while others rescue auxotrophic cells harboring deletions of conditionally essential genes [9,17,18]. Recently, we described a novel protein that supports cell growth by functioning as a bona fide enzyme, both in vitro and in vivo [19].…”
Section: Introductionmentioning
confidence: 99%
“…Protein expression is controlled by a T5 promoter and Lac operator and expression was induced with 100 μg/mL IPTG. The presence of a strong promotor on a high-copy plasmid leads to high levels of protein expression, as has been verified for numerous natural and designed sequences expressed in this system (Patrick et al 2007; Soo et al 2011; Fisher et al 2011; Hoegler and Hecht 2016). …”
Section: Methodsmentioning
confidence: 67%
“…In natural systems, this is a very rare event. However, recent work with large collections of non-natural de novo proteins facilitated our discovery of an entirely novel protein, ConK, with a new function that confers copper resistance in E. coli (Hoegler and Hecht 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, further molecular evolution experiments demonstrated that a de novo protein Syn-IF, an original bifunctional generalist which can rescue two different auxotrophic strains, ΔilvA and Δfes, was evolved into two distinctive monofunctional specialist proteins with enhanced activity (Smith et al 2015). In addition, a de novo protein rescued E. coli from toxic levels of copper (Hoegler and Hecht 2016). Binary code strategy: a semirational approach for creating structural and functional de novo proteins.…”
Section: Semirational Approaches For Creating Structural and Functionmentioning
confidence: 99%